Physicochemical and structural composition of black rice (Oryza sativa) flour from Java, Indonesia - NURHIDAJAH NURHIDAJAH; DIODE YONATA; SUFIATI BINTANAH; BOBY PRANATA (Society for Indonesian Biodiversity, 2024)
Abstract. Nurhidajah, Yonata D, Bintanah S, Pranata B. 2024. Physicochemical and structural composition of black rice (Oryza sativa) flour from Java, Indonesia. Biodiversitas 25: 811-818. Information regarding the characteristics of Indonesian black rice (Oryza sativa) flour from several varieties can provide a scientific base for developing its utilization. This study aimed to compare the physicochemical and structural composition of black rice varieties, namely Cempo Ireng, Melik, Sirampog, and Jeliteng from Java, Indonesia. Black rice was initially crushed to 100 mesh size. The flour's physicochemical and structural composition was then compared descriptively and the quantitative data was analyzed using the SPSS 22.0 software. As a result, significant differences were observed in starch content (68.45-71.08%), amylose content (13.99-18.49%), solubility (13.92-19.55%), swelling power (9.46-11.36%), water binding capacity (74.79-87.87%), and oil binding capacity (59.59-67.33%) of the four varieties of black rice flour. In addition, significant differences were also observed in the paste and thermal properties of various varieties. Morphological analysis shows that the flour structure has a similar shape, which is plate-shaped and contains many flakes. The relative crystallinity of Indonesian black rice flour ranges from 22.95% to 24.25%. This result reflects that all black rice flour particles have an A-type crystalline structure. All varieties of black rice flour have different physicochemical and structural compositions, except crystal structure that shows similarities (type A).